2019
DOI: 10.1088/1674-4926/40/1/012806
|View full text |Cite
|
Sign up to set email alerts
|

Remote plasma-enhanced atomic layer deposition of gallium oxide thin films with NH3 plasma pretreatment

Abstract: High quality gallium oxide (Ga2O3) thin films are deposited by remote plasma-enhanced atomic layer deposition (RPEALD) with trimethylgallium (TMG) and oxygen plasma as precursors. By introducing in-situ NH3 plasma pretreatment on the substrates, the deposition rate of Ga2O3 films on Si and GaN are remarkably enhanced, reached to 0.53 and 0.46 Å/cycle at 250 °C, respectively. The increasing of deposition rate is attributed to more hydroxyls (–OH) generated on the substrate surfaces after NH3 pretreatment, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…In particular, Boschi et al 39 reported ε-Ga 2 O 3 deposited on c-plane sapphire at 550 °C by an unoptimized thermal ALD process (i.e., using water as the oxidant) and indicated that the process conditions need optimization. Hao et al 25 obtained crystalline Ga 2 O 3 films on GaN wafers at 250 °C and observed an epitaxial interface between Ga 2 O 3 and GaN. Roberts et al 32 obtained crystalline gallium oxide films on sapphire at 250 °C which consisted of α-Ga 2 O 3 columns originating from the substrate interface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, Boschi et al 39 reported ε-Ga 2 O 3 deposited on c-plane sapphire at 550 °C by an unoptimized thermal ALD process (i.e., using water as the oxidant) and indicated that the process conditions need optimization. Hao et al 25 obtained crystalline Ga 2 O 3 films on GaN wafers at 250 °C and observed an epitaxial interface between Ga 2 O 3 and GaN. Roberts et al 32 obtained crystalline gallium oxide films on sapphire at 250 °C which consisted of α-Ga 2 O 3 columns originating from the substrate interface.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few literature reports of gallium oxide grown by ALD. , They mostly result in amorphous films that require high-temperature annealing to crystallize. However, there are very few reports ,,,,, of ALD growth of crystalline gallium oxide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ga 2 O 3 can be prepared in five crystallographic stages, namely α, β, γ, δ, and ε, and the β phase is the most used type in electronics applications because of its good chemical and thermodynamic stabilities. [10] Thus far, β-Ga 2 O 3 semiconductors have been prepared using various methods, including molecular beam epitaxy, [11,12] pulsed laser deposition, [13] sputtering, [14] metal-organic chemical vapor deposition, [15] atomic layer deposition, [16] hydride vapor-phase epitaxy, [17] lowpressure chemical vapor deposition, [18] and sol-gel coating. [19] Wafer-scale and high-quality β-Ga 2 O 3 single crystal wafers have also been reported using optical floating zones, [20] Czochralski, [21] and edge-defined film-fed growth [22] methods.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, β ‐Ga 2 O 3 semiconductors have been prepared using various methods, including molecular beam epitaxy, [ 11,12 ] pulsed laser deposition, [ 13 ] sputtering, [ 14 ] metal‐organic chemical vapor deposition, [ 15 ] atomic layer deposition, [ 16 ] hydride vapor‐phase epitaxy, [ 17 ] low‐pressure chemical vapor deposition, [ 18 ] and sol–gel coating. [ 19 ] Wafer‐scale and high‐quality β ‐Ga 2 O 3 single crystal wafers have also been reported using optical floating zones, [ 20 ] Czochralski, [ 21 ] and edge‐defined film‐fed growth [ 22 ] methods.…”
Section: Introductionmentioning
confidence: 99%